Lipoproteins Cause Bone Resorption in a Mouse Model of Staphylococcus aureus Septic Arthritis - Schultz, Michelle; Mohammad, Majd; Nguyen, Minh-Thu; Hu, Zhicheng; Jarneborn, Anders; Wienken, Carina M.; Froning, Matti; Pullerits, Rille; Ali, Abukar; Hayen, Heiko; Götz, Friedrich; Jin, Tao (Frontiers in Microbiology, 2022)
Septic arthritis, most often caused by Staphylococcus aureus (S. aureus), is a rapidly progressive and destructive joint disease with substantial mortality and morbidity. S. aureus lipoproteins (Lpps) are known to induce arthritis and bone destruction. Here, we aimed to investigate the bone resorptive effect of S. aureus Lpps in a murine arthritis model by intra-articular injection of purified S. aureus Lpps, synthetic lipopeptides, and live S. aureus strains. Analyses of the bone mineral density (BMD) of the distal femur bone were performed. Intra-articular injection of both live S. aureus and purified S. aureus Lpps were shown to significantly decrease total- and trabecular BMD. Liquid chromatography–mass spectrometry analyses revealed that the Lpps expressed by S. aureus SA113 strain contain both diacyl and triacyl lipid moieties. Interestingly, synthetic diacylated lipopeptide, Pam2CSK4, was more potent in inducing bone resorption than synthetic triacylated lipopeptide, Pam3CSK4. Modified lipoproteins lacking the lipid moiety were deprived of their bone resorptive abilities. Monocyte depletion by clodronate liposomes fully abrogated the bone resorptive capacity of S. aureus lipoproteins. Our data suggests that S. aureus Lpps induce bone resorption in locally-induced murine arthritis, an effect mediated by their lipid-moiety through monocytes/macrophages.